Developing Cost-Effective Production in Uzbekistan's Textile Industry: Mengembangkan Produksi Hemat Biaya di Industri Tekstil Uzbekistan - Yakhyаeva Inobat (Academia Open, 2023)
This article analyzes the textile industry in Uzbekistan and identifies weaknesses such as outdated machinery, lack of qualified personnel, and low levels of specialization in textile production. The research employs scientific study, comparative comparison, statistical data analysis, and economic comparison to propose solutions such as developing training systems for personnel and introducing modern equipment. Results show a reduction in imports and localization of production, leading to the production of more than 250 types of products and a decrease of 93% in imported products. The implications of this research are relevant to the development of Uzbekistan's textile industry and its economic growth. Highlights: The textile industry is essential to Uzbekistan's economy. Localization of production reduces imports and increases production. Developing personnel and introducing modern equipment are crucial for the industry's growth. Keywords: Uzbekistan, Textile Industry, Cost-Effective Production, Localization, Personnel Development.